1990
DOI: 10.1111/j.1574-6968.1990.tb03814.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizing activity of water- and lipid-soluble phthalocyanines on Escherichia coli

Abstract: Escherichia coli, as most Gram‐negative bacteria, is insensitive to the photosensitizing action of both lipid‐soluble Zinc‐phthalocyanine (Zn‐Pc) and water‐soluble Zinc‐mono/disulfonated phthalocyanine (Zn‐PcS). Photosensitivity can be induced by alteration of the outer membrane, as obtained by either induction of competence or treatment with Tris‐EDTA. Both phthalocyanines largely bind at the level of the cytoplasmic membrane; however, Zn‐PcS shows a superior photosensitizing activity as compared with Zn‐Pc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(110 citation statements)
references
References 8 publications
4
106
0
Order By: Relevance
“…Several studies have demonstrated that Gram-positive bacteria are susceptible to photoinactivation [27][28][29]. On the other hand, Gram-negative bacteria have been resistant to photodynamic action [27,30], unless the permeability of their outer membrane is modified by Tris/EDTA [31] or polymyxin B nonapeptide [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that Gram-positive bacteria are susceptible to photoinactivation [27][28][29]. On the other hand, Gram-negative bacteria have been resistant to photodynamic action [27,30], unless the permeability of their outer membrane is modified by Tris/EDTA [31] or polymyxin B nonapeptide [32].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Gram-negative bacteria have been resistant to photodynamic action [27,30], unless the permeability of their outer membrane is modified by Tris/EDTA [31] or polymyxin B nonapeptide [32]. Gram-negative species have shown enhanced susceptibility to photodynamic action following the application of a PS with cationic charge [33,34] including cationic phenothiazines such as toluidine blue O and methylene blue [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…They are chosen on the basis of their charge, ability to be non-toxic without illumination (dark toxicity) and the ability to become genotoxic or mutagenic following irradiation [23]. Rose Bengal (RB) is a photosensitizer that has been found to be toxic to various microbes, including Streptococcus mutans and Candida albicans, when used with PDT [24,25].…”
Section: Biophotonicsmentioning
confidence: 99%
“…the combined use of photosensitisers and visible light, is considered to be a new potential method for inactivation of microorganisms [1,2,3,4], in the context of the disinfection of water, blood and blood products [5]. A number of photosensitisers are known to be phototoxic towards a variety of Gram-positive bacteria, mycoplasma and yeast [2,6,7]. However, Gram-negative bacteria have not usually been susceptible to photosensitising effects, unless the permeability of their membranes has been artificially increased [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic treatment, i.e. the combined use of photosensitisers and visible light, is considered to be a new potential method for inactivation of microorganisms [1,2,3,4], in the context of the disinfection of water, blood and blood products [5]. A number of photosensitisers are known to be phototoxic towards a variety of Gram-positive bacteria, mycoplasma and yeast [2,6,7].…”
Section: Introductionmentioning
confidence: 99%